Efektivitas dan Keamanan Ceftaroline VS Ceftriaxone dalam Terapi Community-Acquired Pneumonia: Bukti dari Satu Dekade Penelitian - Andi Ameilia Sari Riandika (JURNAL PHARMA BHAKTA, 2025)
Background: Community acquired pneumonia (CAP) remains a leading cause of morbidity and mortality among hospitalized adults. Appropriate selection of empirical antibiotics is crucial to prevent treatment failure and limit antimicrobial resistance. Ceftriaxone has long been the standard empirical therapy for moderate to severe CAP in many clinical guidelines. However, ceftaroline fosamil, a newer generation cephalosporin with activity against Streptococcus pneumoniae (including penicillin resistant strains), has emerged as a potential alternative. Objective: This review aims to evaluate randomized controlled trial (RCT) evidence published between 2015 and 2025 comparing the efficacy and safety of ceftaroline versus ceftriaxone in the treatment of CAP among hospitalized. Methods: A literature search was conducted in PubMed, ScienceDirect, and Scopus for RCTs published between 2015 and 2025 based on the checklist prism. Results: Evidence from RCTs (2015–2025) supports ceftaroline as an effective alternative to ceftriaxone for the management of CAP in hospitalized adults. Several pooled analyses suggest superiority of ceftaroline in terms of clinical cure, while no significant differences were observed in mortality outcomes. The safety profiles of both agents were generally comparable. Conclusion: This review supports ceftaroline as an effective empirical alternative to ceftriaxone for moderate to severe CAP, with evidence indicating potential advantages in clinical cure rates.